Pengolahan Mijel (Minyak Jelantah) Sebagai Peluang Karir Menjadi Lilin Aromaterapi pada Remaja Masjid Al-Ma’Wa Tembung - Alvina Zahra; Budi Dermawan; Nida Fadhila; Selpiyani Br Simanjorang; Syamsuyurnita Syamsuyurnita (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
The use of used cooking oil (mijel) as a raw material in making aromatherapy candles offers career opportunities for students of Al-Ma’wa Tembung Mosque. This community service activity aims to provide training in processing used cooking oil into aromatherapy candles while increasing awareness of the importance of recycling waste oil. The methodology used is practical training, discussion and demonstration. The results of the activity showed high enthusiasm from the participants and the potential for developing aromatherapy candle businesses among teenagers.